Genetic diversity and pathogenic variation in isolates of Exserohilum turcicum causing common leaf blight of sorghum - KUSUM MATHUR, VENKATESH BHAT; SANJAY RATHORE, S. USHA SREE, R. NAGARAJA REDDY S. MURALI MOHAN, R. MADHUSUDHANA* (Indian Phytopathology, 2012)
Leaf blight caused by Exserohilum turcicum is an economically important disease of sorghum in India. Variations in retrotransposon derived random amplified polymorphic DNA (Retro-RAPD) polymorphism and pathogenicity was studied among the 22 isolates of E. turcicum collected from 5 different states of India. The isolates exhibited considerable variation in the pathogenicity on seven sorghum differentials and were assigned to ten pathogenicity groups (P1-P10). Genomic DNA of 22 isolates were profiled with 67 Retro-RAPD primers twice to study genetic variability. A high degree of polymorphism (97%) was observed among the isolates. It was possible to discriminate all the isolates using any one of the 67 primers employed singly or in combination. UPGMA clustering indicated that the isolates shared varied level of genetic similarity ranging from 0.26 to 0.86. All the 22 isolates can be grouped into three major clusters and clustering of isolates was not related with their location of isolation. This is the first report of a molecular as well as pathogenic variability of Indian isolates of E. turcicum collected from sorghum. The retro-RAPD markers can be unequivocally used for fingerprinting fungal isolates and mapping of important pathogenicity-related traits.